1997
DOI: 10.1097/00002030-199708000-00014
|View full text |Cite
|
Sign up to set email alerts
|

On-site, rapid HIV testing with same-day results and counseling

Abstract: Rapid, on-site HIV testing was feasible, preferred by clients, and, resulted in significant improvement in the number of persons learning their serostatus, without increasing the costs or decreasing the effectiveness of counseling and testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
91
1
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(98 citation statements)
references
References 4 publications
4
91
1
2
Order By: Relevance
“…However, use of the Genie II HIV1/HIV2 in Guinea-Conakry would be particularly compromised by the fact that the test requires sera (instead of whole blood) and is subject to cold chain availability, both of which are important operational considerations at peripheral facilities. [21][22][23][24] The First Response HIV Card Test 1-2.0 HIV test is also not recommended as it had a sensitivity that was below the WHO recommended minimum threshold of 99.5%.…”
Section: Discussionmentioning
confidence: 99%
“…However, use of the Genie II HIV1/HIV2 in Guinea-Conakry would be particularly compromised by the fact that the test requires sera (instead of whole blood) and is subject to cold chain availability, both of which are important operational considerations at peripheral facilities. [21][22][23][24] The First Response HIV Card Test 1-2.0 HIV test is also not recommended as it had a sensitivity that was below the WHO recommended minimum threshold of 99.5%.…”
Section: Discussionmentioning
confidence: 99%
“…The Centers for Disease Control (1) has estimated that if a 10-minute rapid test were implemented in public health settings, 700,000 more people would know their HIV serostatus, including 29% more seropositive and 50% more seronegative persons. Rapid testing also may increase testing acceptability by eliminating the current 2-to 4-week wait to receive results (21,81). Studies in a variety of testing venues, including prenatal and family planning clinics, methadone clinics, and STD clinics have shown that delays in scheduling pre-or posttest counseling and client reported difficulties in returning for results deter use of testing (66).…”
Section: Implement New Testing Technologies and Delivery Modalitiesmentioning
confidence: 99%
“…Studies in a variety of testing venues, including prenatal and family planning clinics, methadone clinics, and STD clinics have shown that delays in scheduling pre-or posttest counseling and client reported difficulties in returning for results deter use of testing (66). Rapid testing in a Texas anonymous test site resulted in a 4% increase in seronegative persons and a 16% increase in seropositive persons being tested; a 210% increase in seronegative persons and a 23% increase in seropositive persons being tested in an STD clinic (81). International studies also support the efficacy and reliability of rapid testing (82)(83)(84).…”
Section: Implement New Testing Technologies and Delivery Modalitiesmentioning
confidence: 99%
“…Advances in laboratory assays, particularly "rapid tests," have facilitated an increase in the testing and detection of HIV infection, because rapid HIV tests enable individuals to receive their results during the same appointment as the sample collection. There is evidence that individuals who undergo rapid HIV testing are significantly more likely to receive their results than those who undergo the traditional HIV antibody ELISA test (Antonio-Gaddy et al, 2006;Guenter et al, 2008;Kassler, Dillon, Haley, Jones, & Goldman, 1997;Kelen, Shahan, Quinn, & The Project Educate Work Group, 1999;Lubelcheck et al, 2005;Spielberg et al, 2005;Wurcel, Zaman, Zhen, & Stone, 2005).…”
mentioning
confidence: 99%
“…Prior studies have reported that between 50% and 100% of individuals who receive a reactive rapid HIV test take a confirmatory HIV test (Antonio-Gaddy et al, 2006;Begley et al, 2008;Brown et al, 2007;CDC, 2007;Guenter et al, 2008;Kelen et al, 1999) and between 49% and 100% of the individuals who receive a confirmatory HIV test return for the results (Antonio-Gaddy et al, 2006;Begley et al, 2008;Bucher et al, 2007;CDC, 2007;Delaney et al, 2011;Freeman, Sattin, Miller, Dias, & Wilde, 2009;Guenter et al, 2008, Kassler et al, 1997Spielberg et al, 2005). To date, no studies have examined the predictors of returning for confirmatory HIV test results.…”
mentioning
confidence: 99%